On the metacognitive dimension of suspended syntactic constructions. A descriptive study on aphasic Spanish speakers - Hernández-Sacristán, Carlos; Serra-Alegre, Enrique (Revista de Investigación en Logopedia, 2016)
By taking into consideration conversational outputs from aphasic Spanish speakers, a functional characterisation of suspended syntactic constructions will be provided here. Suspensions of syntactic constructions may be initially thought of as attributed to a language processing deficit in people with aphasia, which is, in fact, only partly the case. An examination of conversational data demonstrates, however, that a comprehensive explanation of syntactic suspensions requires a re-assessment of this phenomenon in the realm of meta-cognitive processes associated with language behaviour. Five general types of procedures and contexts for suspended syntactic constructions will be proposed and discussed in this paper. They differentially involve a series of metacognitive processes such as monitoring for anticipation and prevention of foreseeable mistakes, intersemiotic control of language production and communication by the use of gesturing, motivational and intentional aspects associated with language use, collaborative tasks in language production and theory of mind phenomena.